Comparative seismic loss analysis of an existing non-ductile RC building based on element fragility functions proposals. (15th December 2018) - Romano, Fabio; Faggella, Marco; Gigliotti, Rosario; Zucconi, Maria; Ferracuti, Barbara
Highlights: Importance of IM selection in propagation of uncertainties to seismic loss analysis. Influence of structural model configuration on direct losses. Influence of proposed element fragility functions on seismic losses estimate. Proposals of consequence functions for beam-column joints and masonry infill walls. Quantitative estimation of indirect losses, based on past Italian earthquakes. Influence of dispersions in probabilistic direct losses on the EAL estimate. Abstract: A comparative seismic loss analysis is presented for a non-ductile infilled reinforced concrete building evaluating the influence on direct economic losses of different parameters characterizing a building performance model. Propagation of uncertainties to seismic repair cost estimate is investigated in terms of effect of input intensity measures, definition of element fragility and consequence functions specific to non-ductile RC buildings through incremental dynamic analyses and probabilistic performance-based earthquake engineering methodologies. A set of element fragility and consequence functions has been proposed based on experimental data for internal and external beam column joints and on analytical models for masonry infill walls. A quantitative estimate of indirect losses is proposed based on past earthquakes data, incorporating the building inactivity and the delay in the beginning of the reconstruction process. Seismic loss assessment is presented at single hazard levels and critically compared, providing insight into different possible alternatives for performance models implementation. A fully probabilistic life-cycle analysis is carried out to present realistic risk analysis figures for non-ductile reinforced concrete buildings.